Introduction and Utilization of Plants in the Wild for Prospective Members of Mapala Batch XXVII Mapala Paksi Arga Padang Institute of Technology: Pengenalan dan Pemanfaatan Tumbuhan Di Alam Bebas bagi Calon Anggota Mapala Angkatan XXVII Mapala Paksi Arga Institut Teknologi Padang - Gustina Indriati; Jasmi; Friska Eka Fitria; Weny Murdina (Journal of Community Service and Application of Science, 2022)
Nature lover student (mapala) students who often carry out natural exploration activities. Mapala must have the ability to survive and recognize plants that are useful for food and medicine. The limited information that Mapala has about plants in the wild indicates that they need relevant and accountable sources to be able to survive in difficult times. One way to provide sources of information to students is through counseling. The methods used in carrying out this activity are lectures or counseling, discussions, demonstrations, and evaluations. Data collection techniques during counseling using questionnaires and interviews. The counseling activity was carried out at the Paksi Arga Nature Lovers Student Group, Padang Institute of Technology. The participants in this activity were attended by 15 nature-loving students at the Paksi Arga Institute of Technology and the organizers consisted of 4 lecturers and 2 students. The output results of the independent t-test show that the Sig value is <0.05, so there is a significant difference between mapala knowledge before and after counseling. Difference in percentage There is an increase in knowledge that plants that can be used for survival are as big as20,6%, edible plants for survival 27%, and plants that can be used as medicine 22,64%.